2011
DOI: 10.1371/journal.pone.0019772
|View full text |Cite
|
Sign up to set email alerts
|

The Proteolipid Protein Promoter Drives Expression outside of the Oligodendrocyte Lineage during Embryonic and Early Postnatal Development

Abstract: The proteolipid protein (Plp) gene promoter is responsible for driving expression of one of the major components of myelin – PLP and its splice variant DM-20. Both products are classically thought to express predominantly in oligodendrocytes. However, accumulating evidence suggests Plp expression is more widespread than previously thought. In an attempt to create a mouse model for inducing oligodendrocyte-specific gene deletions, we have generated transgenic mice expressing a Cre recombinase cDNA under control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 35 publications
1
35
0
Order By: Relevance
“…To examine whether mutant Htt is expressed in oligodendrocytes at the endogenous level, we crossed HD 140CAG knock-in (KI) mice with transgenic mice that selectively express GFP in oligodendrocytes under the control of the proteolipid protein ( PLP ) gene promoter (Mallon et al, 2002), which drives transgene expression predominantly in oligodendrocytes in adult mouse brain (Michalski et al, 2011). The crossed mice would thus allow us to define whether full-length mutant Htt is expressed in GFP-positive oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether mutant Htt is expressed in oligodendrocytes at the endogenous level, we crossed HD 140CAG knock-in (KI) mice with transgenic mice that selectively express GFP in oligodendrocytes under the control of the proteolipid protein ( PLP ) gene promoter (Mallon et al, 2002), which drives transgene expression predominantly in oligodendrocytes in adult mouse brain (Michalski et al, 2011). The crossed mice would thus allow us to define whether full-length mutant Htt is expressed in GFP-positive oligodendrocytes.…”
Section: Resultsmentioning
confidence: 99%
“…Conditional expression of DTau was obtained by using the PLPERT mouse line [45], which has been widely used with consistent high-efficiency recombination [46,53,54]. It is known that PLP is exclusively expressed in mature OLGs; however, adult CNS is known to contain a population of NG2 cells that express PLP [55].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that PLP is exclusively expressed in mature OLGs; however, adult CNS is known to contain a population of NG2 cells that express PLP [55]. Michalski et al [46] showed that PLP promoter-driven expression occurs in NG2 cells and progressively diminishes from 20 to 5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OPCs express specific antigens such as platelet-derived growth factor alpha receptor (PDGFaR) and chondroitin sulfate proteoglycan NG2 (Stallcup and Beasley 1987;Nishiyama et al 1996;Butt et al 1999). Recent studies have shown that OPCs can be selectively detected in transgenic mice encoding a reporter gene driven by specific promoters including proteolipid protein (PLP) (Mallon et al 2002;Michalski et al 2011), PDGFaR (Rivers et al 2008;Boda et al 2015), and NG2 (Zhu et al 2008;Komitova et al 2011). While PLP gene shows many splicing variants in mice and humans (Bongarzone et al 1999;Li et al 2009;Sarret et al 2010), only PLP and DM-20 mRNA transcripts were identified as splicing variants encoded by PLP gene in rats (Sarret et al 2010).…”
Section: Introductionmentioning
confidence: 99%